2011
DOI: 10.1017/s0952675711000224
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic invariance in the phonetic expression of syllable structure: a case study of Moroccan Arabic consonant clusters

Abstract: We asked whether invariant phonetic indices for syllable structure can be identified in a language where word-initial consonant clusters, regardless of their sonority profile, are claimed to be parsed heterosyllabically. Four speakers of Moroccan Arabic were recorded, using Electromagnetic Articulography. Pursuing previous work, we employed temporal diagnostics for syllable structure, consisting of static correspondences between any given phonological organisation and its presumed phonetic indices. We show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(78 citation statements)
references
References 49 publications
3
75
0
Order By: Relevance
“…the timing of the prevocalic consonant relative to the vowel does not differ between CCCV, CCV, and CV forms. This has been found to be the case in Moroccan Arabic [64], Slovak [65], Tashlhiyt Berber [66], [67], and for/sC/ clusters in Italian [26], where non-prevocalic word-initial consonants are not syllabified as onsets. This pattern can be understood to arise when all consonants except for the prevocalic one are sequentially selected and hence do not influence the coordinative interactions between the prevocalic consonant and vowel.…”
Section: Resultsmentioning
confidence: 92%
“…the timing of the prevocalic consonant relative to the vowel does not differ between CCCV, CCV, and CV forms. This has been found to be the case in Moroccan Arabic [64], Slovak [65], Tashlhiyt Berber [66], [67], and for/sC/ clusters in Italian [26], where non-prevocalic word-initial consonants are not syllabified as onsets. This pattern can be understood to arise when all consonants except for the prevocalic one are sequentially selected and hence do not influence the coordinative interactions between the prevocalic consonant and vowel.…”
Section: Resultsmentioning
confidence: 92%
“…In a simplex onset language, Moroccan Arabic, Shaw et al (2011) found evidence for right-edge stability predominately, but also cases where (three out of four) speakers, who in most contexts showed right-edge stability, exhibited C-center stability. In these latter 'exceptional' cases, Shaw et al observed that the syllable duration in the CV sequence was longer compared to the CCV sequence (equivalently, the CV portion of the phonetic string compressed in duration from the CV to the CCV context).…”
Section: Discussionmentioning
confidence: 90%
“…They thus proposed that invariances characterizing the relation between syllabic organization and phonetics are dynamic as opposed to static. Gafos et al (2014) pursued further analysis of the experimental and computational result of Shaw et al (2011). In their study, the statistics of syllabic organization were expressed in equations involving estimates of continuous phonetic parameters expressing the timing of consonants and vowels: consonantal plateau durations, vowel durations, and their variances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated measures ANOVAs across the five Speakers were applied in this case, as opposed to separate ANOVAs per Speaker, because of the limited number of values used per Speaker for this analysis (a single value per Stress condition) (cf. Shaw, Gafos, Hoole and Zeroual, 2011). Both main and interaction effects were assessed, and in case of a significant effect, post-hoc pair-wise comparisons using the Bonferroni adjustment were performed.…”
Section: 0 Resultsmentioning
confidence: 99%